Schistosoma mansoni (Platyhelminthes, Trematoda) nuclear receptors: Sixteen new members and a novel subfamily - Wu, Wenjie; Niles, Edward G.; Najib M. El‐Sayed; Berriman, Matthew; LoVerde, Philip T. (GeneGene, 2006)
Nuclear receptors (NRs) are important transcriptional modulators in metazoans. Sixteen new NRs were identified in the Platyhelminth trematode, Schistosoma mansoni. Three were found to possess novel tandem DNA-binding domains that identify a new subfamily of NR. Two NRs are homologues of the thyroid hormone receptor that previously were thought to be restricted to chordates. This study brings the total number of identified NR in S. mansoni to 21. Phylogenetic and comparative genomic analyses demonstrate that S. mansoni NRs share an evolutionary lineage with that of arthropods and vertebrates. Phylogenic analysis shows that more than half of the S. mansoni nuclear receptors evolved from a second gene duplication. As the second gene duplication of NRs was thought to be specific to vertebrates, our data challenge the current theory of NR evolution.
Keywords: Nuclear receptors; Schistosoma mansoni